(untitled) (Global Journal of Medical Research, 2018)
Pulmonary Langerhans cell histiocytosis (PLCH) is a rare pulmonary disorder with characteristic imaging features. It usually affects young adults and is associated with cigarette smoking. PLCH is listed in the gamut for cystic lung disease and should be considered by the radiologist if the appropriate findings are identified. The authors report an advanced case of PLCH in a young male with a smoking load of 6 pack-year. The prognosis is variable with frequent regression, stabilization, or recurrence of disease.